Tweeters, Woofers and Horns: The Complex Orchestration of Calcium Currents in T Lymphocytes - Nohara, Lilian L. (Front Immunol, 2015)
Elevation of intracellular calcium ion (Ca(2+)) levels is a vital event that regulates T lymphocyte homeostasis, activation, proliferation, differentiation, and apoptosis. The mechanisms that regulate intracellular Ca(2+) signaling in lymphocytes involve tightly controlled concinnity of multiple ion channels, membrane receptors, and signaling molecules. T cell receptor (TCR) engagement results in depletion of endoplasmic reticulum (ER) Ca(2+) stores and subsequent sustained influx of extracellular Ca(2+) through Ca(2+) release-activated Ca(2+) (CRAC) channels in the plasma membrane. This process termed store-operated Ca(2+) entry (SOCE) involves the ER Ca(2+) sensing molecule, STIM1, and a pore-forming plasma membrane protein, ORAI1. However, several other important Ca(2+) channels that are instrumental in T cell function also exist. In this review, we discuss the role of additional Ca(2+) channel families expressed on the plasma membrane of T cells that likely contribute to Ca(2+) influx following TCR engagement, which include the TRP channels, the NMDA receptors, the P2X receptors, and the IP(3) receptors, with a focus on the voltage-dependent Ca(2+) (Ca(V)) channels.